Pyrrolo[2,1-c][1,4]benzodiazepine-5,11-dithione - Ourahou, S.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The seven-membered fused-ring in the title compound, C(12)H(12)N(2)S(2), adopts a boat conformation (with the two phenylene C atoms representing the stern and the methine C atom the prow). This methine C atom and the tertiary N atom also belong to a five-membered ring, which has an envelope conformation. In the crystal structure, molecules are linked about a center of inversion by pairs of N-H center dot center dot center dot S hydrogen bonds.